Continuity and innovation in the Aramaic legal tradition - Gross, Andrew D. (Supplements to the Journal for the study of Judaism, 2008)
This book argues that Aramaic scribes from antiquity drew upon a common legal tradition. It identifies the distinctive elements that form the core of this tradition and traces their antecedents within the cuneiform record.